Firm-to-Firm Relationships and the Pass-Through of Shocks: Theory and Evidence - Heise, Sebastian (The Review of Economics and Statistics, 2024)
Abstract Economists have long suspected that firm-to-firm relationships might lower the responsiveness of prices to shocks due to the use of fixed-price contracts. Using transaction-level U.S. import data, I show that the pass-through of exchange rate shocks in fact rises as a relationship ages. Based on novel stylized facts about a relationship's life cycle, I develop a model of relationship dynamics in which a buyerseller pair accumulates relationship capital to lower production costs under limited commitment. The structurally estimated model generates countercyclical mark-ups and countercyclical pass-through of shocks through variation in the economy's rate of relationship creation, which falls in recessions.